TRANSAKSI CRYPTOCURRENCCY BERDASARKAN HUKUM ISLAM DI INDONESIA (Fakultas Hukum Universitas Malikussaleh, 2022)
Based on the research conducted that the view of Islamic law forbids Cryptocurrency transactions because it contains elements of gharar and dharar and is not in accordance with Law Number 7 of 2011 concerning currencies and Bank Indonesia regulations Number 17 of 2015 concerning the obligation to use Rupiah in the State of Indonesia. The Minister of Trade Number 99 of 2018 allows it as a Commodity asset in accordance with the supervision of CoFTRA and does not allow Cryptocurrency as a means of payment. In the supervision of cryptocurrencies, the government has issued regulations through Law No. 10 of 2011 concerning Commodity Futures Trading. Meanwhile, in terms of preventing Cryptocurrency in Indonesia, the prudential banking principle is regulated in Bank Indonesia Regulation No. 14/27/PBI/2012.